A Comparison of Efficacy of Platelet-Rich Plasma (PRP) and Platelet-Rich Fibrin (PRF) in the treatment of Post-Acne Scars - Fayyaz, Aneeqa; Gulzar, Koukab; Hussain, Ruhma; Munir, Saeeda (Indus Journal of Bioscience Research, 2025)
Objective: To compare the efficacy of Platelet-Rich Plasma (PRP) and Platelet-Rich Fibrin (PRF), in the treatment of post-acne scars. Study design: Prospective, split-face, randomized controlled trial. Place and duration of study: Department of Dermatology, KRL Hospital, Islamabad, from April 2024 to September 2024. Methods: A total of 50 patients aging between 18-45 years, reporting with post-acne scars of varying severities were included in this study. Left sides of faces of all study participants were selected as PRP side where intradermal injections of platelet-rich plasma (PRP) at 0.1 mL per injection were injected into atrophic scars, while right sides of faces were selected as PRF side where intradermal injections of platelet-rich fibrin (PRF) at 0.1 mL per injection were injected into atrophic scars (1.5 to 2 cm apart). Subsequently, all the patients were treated with a dermapen (micro-needling) in four directions. Assessment of severity of acne scars was done by employing the Goodman and Baron’s Global Scarring Grading System. The primary outcome was the improvement in post-acne scars assessed by this grading system four weeks after the last session. Results: Mean age of study participants was 27.68±4.93 years with age ranging from 19 to37 years. Male gender was 58% of total study population while female gender was 42%. The results of the primary outcomes of the study showed that PRF was significantly more effective than PRP in the treatment of post-acne scars, as evaluated by Global Scarring Grading System scores (p=0.001) and quartile grading (p=0.007). Conclusion: The method of PRF is significantly more effective than PRP is the treatment of acne scars. The two treatments are equally acceptable regarding the incidence of adverse events.